ENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK DISKUSI TERHADAP KEMAMPUAN KOMUNIKASI ANTAR PRIBADI SISWA KELAS XI DI SMK PELITA ALAM BEKASI - Fadhil Hardiansyah; Dita Rizki Prasitia (Guidance : Jurnal Bimbingan dan Konseling, 2016)
The influence of technical discussion group tutoringservice of interpersonal communication skills of students of Class XI in SMK Lamp NatureBekasi. Thesis: the educational guidance counseling Degree programs the University of IslamAS'SYAFI ' IYAH JOIN, 2015.This research aims to know the influence or whether tutoring service engineeringgroup discussion of interpersonal communication skills of students. The hypothesis putforward in the study is "the effect of group guidance services technique discussion ofinterpersonal communication skills of students". This research was carried out in Bekasi onNatural Lamp SMK class XI semester even 2014/2015. Polupasi with 80 students. 40students class experiments and 40 grade control. The samples studied as many as 40students.This research uses experimental design method of non-equivalent control groupdesign. Free variables: technical discussion group for guidance. Bound variables: personalcommunication anta students. Interpersonal communication instrument students using thelikert scale with shape tests. with statement and answer choice SS, S, CS, KS, TS.To test the validity of the instrument is obtained is r-count will be consulted with rcriticism (Pearson product moment correlation table). With n = 62 at 5% significance leveli.e. r criticism = 0.25. If r-r-> count table (0.063 > 0.25.) then the item is said to be valid andcan be used for data collection. Reliability tests for testing communication between privatestudents who are fully tested, gained 0.86 = rhitung > 0.25 so that this research instrumentreliability. Before data analysis and test research on liliefors, its homogeneity test, test andtest result t. normality indicates that results for pretest postest to Lhitung less than Ltabel(Lhitung < Ltabel) on a significant level of α = 0.05. with n = 40 results pretes and postesclass experiment and control, experimental pretest = 0,087 postest experiment = 0.14 < 0,086< 0.14 and pretest control = 0.14 postest control 0,112 < = 0,115 < 0.14. then it can beconcluded both samples Gaussian normal.The test results show that its homogeneity on a significant level of α = 0.05 Fhitungresult experiments in class 0.27 < Ftabel 1.70 and school classrooms; control Fhitung 0,907 <Ftabel 1,704. it can be concluded that both data have a homogeneous variances. After donetest requirement analysis, hypothesis testing is done next by using test-t test calculationsbased on results.-q. retrieved thitung 23,43 whereas in α = 0.05 significant level ttabel 2,023.therefore thitung = 23,43 > ttabel 2,023, H0 is rejected and then accepted Ha. And the resultsof this study concluded that there was a significant effect of group guidance Servicestechnique discussion of interpersonal communication skills of students.